PEMBERDAYAAN UMKM DI DESA MEKARSARI KECAMATAN CARENANG KABUPATEN SERANG - Encep Saefullah; Arifah Imanun; Aldi Maulana; Rosa Yunika; Anisa Nurtriyani; Dhea Natasya Alamsyah; Bisma Ikhsanudin; Rizki Mulyadi (Indonesian Collaboration Journal of Community Services, 2023)
SMEs in Mekarsari Village are Crackers SMEs. The problems that occur are related to marketing activities that are still conventional and production that still uses traditional tools so that they have an impact on sales volume and product quality. This service activity aims to provide education to MSMEs in the form of counseling in the context of empowering MSMEs by using digital media and using Appropriate Technology (TTG) to maximize the production process. As a result of implementing this activity, MSMEs in their marketing have used digital media, have business legality, innovations in the form of product packaging and the use of machines in their production